MULTIMEDIA MICROLEARNING CREATION TRAINING SMP IT ATTIN WEST SUMATERA - Liza Yulia Sari; vivi fitriani; Diana Susanti; Wira Solina (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
Microlearning is small-scale learning containing content designed into small segments through various media formats, so that the available information becomes "short content" which allows someone to quickly understand the material in the content and can learn anywhere and at any time through technology, information and communication devices. . Microlearning is created in various formats such as podcasts, PowerPoint slides, infographics, motion graphics, explainer videos, as well as interactive video conferences and gamification. Microlearning makes learning easier to understand, remembered for a long time, increasing the effectiveness and efficiency of PBM. The aim of the training in this community service activity is to provide knowledge and skills for teachers at SMP IT Attin West Sumatra to be able to produce more interesting media and increase students' interest in learning and achieve learning goals.The result of this service is an increase in teacher knowledge and skills in being able to produce microlearning that is appropriate to the subjects being taught.